2022
DOI: 10.1021/acs.jafc.1c05115
|View full text |Cite
|
Sign up to set email alerts
|

Water-In-Oil Pickering Emulsions Stabilized by Microcrystalline Phytosterols in Oil: Fabrication Mechanism and Application as a Salt Release System

Abstract: Recently, Pickering emulsions stabilized by edible particles have attracted significant attention from the scientific community and food industry owing to their surfactant-free character. However, those edible particles are mostly used for stabilizing oil-in-water emulsions, whereas those for water-in-oil emulsions are very limited. In this article, stable water-in-oil Pickering emulsions were prepared through dispersing phytosterol particles in oil phase, and the effects of antisolvent treatment, the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In our previous work, we confirmed that hydrophobic M. neoaurum cells act as solid particles to stabilize W/O Pickering emulsions [15]. It has also been reported that phytosterol crystals act as solid particles to stabilize W/O Pickering emulsions [24]. Furthermore, adsorption of M. neoaurum cells onto phytosterol crystals to form crystal phytosterol-bacteria microaggregates, which has been confirmed by CLSM analysis, exhibits wettability unlike that of crystal phytosterol particles or bacteria [16].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our previous work, we confirmed that hydrophobic M. neoaurum cells act as solid particles to stabilize W/O Pickering emulsions [15]. It has also been reported that phytosterol crystals act as solid particles to stabilize W/O Pickering emulsions [24]. Furthermore, adsorption of M. neoaurum cells onto phytosterol crystals to form crystal phytosterol-bacteria microaggregates, which has been confirmed by CLSM analysis, exhibits wettability unlike that of crystal phytosterol particles or bacteria [16].…”
Section: Discussionsupporting
confidence: 81%
“…1), and it had already been confirmed that the Pickering emulsions were stabilized by phytosterol crystals as solid emulsifiers [16]. Very recently, phytosterol crystals have also been utilized as emulsifiers for the fabrication of eatable W/O Pickering emulsions in the food field [24]. With the progress of microbial transfor-…”
Section: Time Course Of Microbial Transformationmentioning
confidence: 96%
“…Due to the significant health risks associated with a high-salt intake, the development of salt-reducing foods has received growing attention [ 196 ]. In this context, Wang et al [ 197 ] discussed a promising method for regulating the salinity by reducing the sodium content through the emulsion-based delivery of NaCl.…”
Section: Applications On the Macrostructure Scalementioning
confidence: 99%
“…Biopolymer-based food-grade nanoparticles (e.g., protein, 24 polysaccharide, 25 and lipid) which play the role of Pickering emulsion stabilizers have attracted formulation scientists and gained increasing popularity in the past couple of years. 26 Soybean, a kind of abundant natural resource, possesses excellent nutritional value and low production costs. 27 Besides, soy protein isolate (SPI), possessing 18 diverse amino acids, is an enriched commercial form of soy protein.…”
Section: ■ Introductionmentioning
confidence: 99%